Operations management in the supply chain : sustainability and resilience - Schroeder, Roger G.; Goldstein, Susan Meyer (New York, NY : McGraw Hill LLC, 2024)
"Operations and supply chain management is an exciting and vital field in today's complex business world. Therefore, students in both MBA and undergraduate courses have an urgent need to understand operations-an essential function in every business"--
Includes index.
Ages 18+
Keywords: Production management; Production management -- Case studies; Decision making